Naturally occurring BRCA2 alternative mRNA splicing events in clinically relevant samples. Issue 8 (8th April 2016) - Fackenthal, James D; Yoshimatsu, Toshio; Zhang, Bifeng; de Garibay, Gorka R; Colombo, Mara; De Vecchi, Giovanna; Ayoub, Samantha C; Lal, Kumar; Olopade, Olufunmilayo I; Vega, Ana; Santamariña, Marta; Blanco, Ana; et al.
Abstract : Background: BRCA1 and BRCA2 are the two principal tumour suppressor genes associated with inherited high risk of breast and ovarian cancer. Genetic testing of BRCA1 /2 will often reveal one or more sequence variants of uncertain clinical significance, some of which may affect normal splicing patterns and thereby disrupt gene function. mRNA analyses are therefore among the tests used to interpret the clinical significance of some genetic variants. However, these could be confounded by the appearance of naturally occurring alternative transcripts unrelated to germline sequence variation or defects in gene function. To understand which novel splicing events are associated with splicing mutations and which are part of the normal BRCA2 splicing repertoire, a study was undertaken by members of the Evidence-based Network for the Interpretation of Germline Mutant Alleles (ENIGMA) consortium to characterise the spectrum of naturally occurring BRCA2 mRNA alternate-splicing events. Methods: mRNA was prepared from several blood and breast tissue-derived cells and cell lines by contributing ENIGMA laboratories. cDNA representing BRCA2 alternate splice sites was amplified and visualised using capillary or agarose gel electrophoresis, followed by sequencing. Results: We demonstrate the existence of 24 different BRCA2 mRNA alternate-splicing events in lymphoblastoid cell lines and both breast cancer and non-cancerous breast cell lines. Conclusions: These naturally occurring alternate-splicing events contribute to the array of cDNA fragments that may be seen in assays for mutation-associated splicing defects. Caution must be observed in assigning alternate-splicing events to potential splicing mutations.